ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT INVESTASI DI DAERAH : STUDY KASUS DI KABUPATEN JEMBER JAWA TIMUR - Hanim, Anifatul; Ragimun, Ragimun (Badan kebijakan Fiskal, 2010)
The trend of economic growth in Jember region is tremendously sophisticated. It needs more resources support especially from potential investors either government or private sector. Investigation on the partner's environments is normally been conducted before coming to the field. The perceptions of this potential investor will derive their expectation and contribute significantly to investment climate in Jember. The aims of this research are: (1) to determine the economic and non economic potential factors in Jember region and to attract the investors (2) to test the reliability and validity of the potential factors. Besides twenty two economic and non economic factors, there are six variables produced by EFA method. These variables are potentially influence the investors' attractiveness. There are economic stabilization, administration, government policy, institutional, and securities. Reliability and validity test imply that the factors are able for further statistical analysis.